Application of HPFRCC in beam–column joints to reduce transverse reinforcements. (June 2021) - Saghafi, Mohammad Hossein; Golafshar, Ali; Zareian, Mohammad Sajjad; Mehri, Amir Hossein
Abstract: In this paper, in order to prevent the congestion of transverse reinforcements in beam-column joints of reinforced concrete frames which meet special seismic regulations, high-performance fiber reinforced cement composites (HPFRCC) with a combination of double hooked-end steel fibers and steel microfibers were used. For this purpose, four external beam-column joints were constructed to a scale of 1/2 and the specimens were tested under cyclic loading. The tested specimens include a normal concrete one meeting special seismic regulations as the control specimen and three HPFRCC ones made by reducing the transverse reinforcement in the beam and column. Hysteresis behavior, load-carrying capacity, energy dissipation and cracking patterns were analyzed and compared with the cyclic response of the control specimen for all experimental specimens. The test results indicate that the HPFRCC specimens, in comparison with the control specimen, have higher stiffness, load-carrying capacity and energy dissipation. Moreover, HPFRCC joints show a better damage tolerance capacity than the control specimen at higher drifts. Furthermore, the results of this study indicate that the use of HPFRCC in joint can be a proper strategy for increasing shear capacity and reducing the amount of beam and column transverse reinforcements.